Analisis strategi keunggulan bersaing dengan pendekatan analisis SWOT pada Spartan Gym Pekanbaru - Susyenni Wanti; Taufiqurrahman '; Deny Danar Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Increase rate of migration to Riau especially Pekanbaru city cause an increase and growth fitness industry in Pekanbaru led to competititon between companiesnthat is getting touger. This research that aims to describe how strategy that gives an advantage in competition with Spartan Gym Pekanbaru, to analysis environment condition of external and internal by used SWOT analysis and plan alternative strategy to Spartan Gym Pekanbaru at Jl. Wonosari No.6 Pekanbaru. Method that we used in this research is qualitative method. The result of research shows internal factor of Spartan Gym pros is the image of company that have know, company’s uniqueness, facilities and qualities good service, cozy and clean room, and the cons is the location is not strategic, low marketing, the customer service is not friendly and undifferent service. While from the external factor is chance to open new branch, opportunity to cooperation with the other, competitor and the new rival. Based on that factors, Spartan Gym stand on defensive position where company have to do their concentration defensive strategy or focus to plan to business development for Spartan Gym Pekanbaru as fitness center.Keywords : Analysis of competitive advantage, SWOT Analyis, and fitness center.